2014
DOI: 10.1057/bm.2014.15
|View full text |Cite
|
Sign up to set email alerts
|

The effects of affective and utilitarian brand relationships on brand consideration

Abstract: Most consumer brand relationship research concentrates on understanding the relationship between the consumer and the brand, and very little research investigates the consequences of those relationships. Given the plethora of brands on the market, each competing for the attention of the consumer and the opportunity to build a relationship with the consumer, understanding the effects of consumer-brand relationships (CBR) provides vital information to the brand manager about the types of brand relationships to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 89 publications
(119 reference statements)
1
14
0
Order By: Relevance
“…That is why brand positioning must serve the needs and preferences of consumers, offering them the right value proposition based on the market (Armstrong and Kotler 2015;Bhat and Reddy 1998;Sheth 2011). In developed economies, international competition is so fierce that consumers are looking for more trustworthy relationships with brands and thus are more emotionally engaged with them (Granitz and Forman 2015;Leung et al 2014;Wee and Ming 2003). In emerging economies, since consumers have been absent from the global market, they are then less experienced and might behave more rationally than their counterparts in developed economies (Zarantanello et al 2013).…”
Section: Are Brand Benefits Perceived Differently In Less Developed Ementioning
confidence: 99%
“…That is why brand positioning must serve the needs and preferences of consumers, offering them the right value proposition based on the market (Armstrong and Kotler 2015;Bhat and Reddy 1998;Sheth 2011). In developed economies, international competition is so fierce that consumers are looking for more trustworthy relationships with brands and thus are more emotionally engaged with them (Granitz and Forman 2015;Leung et al 2014;Wee and Ming 2003). In emerging economies, since consumers have been absent from the global market, they are then less experienced and might behave more rationally than their counterparts in developed economies (Zarantanello et al 2013).…”
Section: Are Brand Benefits Perceived Differently In Less Developed Ementioning
confidence: 99%
“…To go along with the previous findings, this study examined two service categories (fast food vs. banking services) that represented different relationship forms as explained in the section on research method below. Following the study by Leung et al (2014), this research also conceived consumer-brand relationship as a second order construct consisting of an affective dimension (measured by love/passion, self-connection and interdependence) and a utilitarian dimension (measured by commitment, intimacy and brand partner quality).…”
Section: Consumer-brand Relationshipmentioning
confidence: 99%
“…For example, Asworth et al (2009) indicated that utilitarian brand attributes may contribute to strong consumer-brand relationships. Leung et. al.…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations